Stages of development of the Holocene channel in the Warta valley, Koźmin-KN site - Twardy, Juliusz; Petera-Zganiacz, Joanna; Dzieduszyńska, Danuta; Forysiak, Jacek; Milecka, Krystyna; Okupny, Daniel; Rudna, Marta; Stachowicz-Rybka, Renata; Skoczylas-Śniaz , Sylwia (Acta Geographica Lodziensia, 2024)
In the article, the authors analyse the filling of a small palaeochannel of the Warta River cut in the flat and monotonous surface of a low terrace at the beginning of the Holocene. Two stages were distinguished in the development of the studied channel – limnic, which was recorded in the Preboreal and Boreal by the accumulation of nearly 1-metre-thick gyttja at the bottom of the channel filling, and the fluvial stage, related to the functioning of the active channel and recorded by a sequence of mainly mineral alluvium. The entire channel filling was examined with sedimentological methods, while the gyttja was investigated using palaeobiological methods (palynology, plant macrofossil, fossil Cladocera), geochemical method, geo-chronological method (14C) and also physicochemical features. For the limnic stage, changes in the level of water in a small lake occupying the studied palaeochannel and fluctuations in the trophy were partially determined. The reconstructions also included the evolution of vegetation, faunal elements (Cladocera), fluctuations in the content of organic matter, pH, conductivity and chemical elements..